Comparison of DMEK and DSAEK in Eyes With Endothelial Decompensation After Previous Penetrating Keratoplasty. Issue 9 (September 2021) - Kiel, Marian; Bu, Julia Bing; Gericke, Adrian; Vossmerbaeumer, Urs; Schuster, Alexander K.; Pfeiffer, Norbert; Wasielica-Poslednik, Joanna
Abstract : Purpose: Posterior lamellar keratoplasty is increasingly applied in patients with endothelial decompensation after penetrating keratoplasty (PK). The aim of this study was to compare the results of Descemet membrane endothelial keratoplasty (DMEK) and Descemet stripping automated endothelial keratoplasty (DSAEK) after PK. Methods: In this retrospective study, clinical data of 30 patients who received DMEK (n = 19) or DSAEK (n = 11) for endothelial decompensation after PK were evaluated. All lamellar keratoplasties were performed at the Department of Ophthalmology at University Hospital Mainz, Germany. Primary end point included best-corrected visual acuity, and secondary end points included endothelial cell density, rebubbling, and rejection rates, all at 6 and 12 months. Results: After 6 months and 12 months, 89% of DMEK and 73% of DSAEK grafts and 63% of DMEK and 64% of DSAEK grafts provided sufficient corneal deturgescence, respectively, represented by improvement in best-corrected visual acuity. DMEK group median preoperative Logarithm of the Minimum Angle of Resolution visual acuity of 1 increased to 0.5 after 6 and 12 months. DSAEK group median Logarithm of the Minimum Angle of Resolution visual acuity increased from 3 to 2 and 1.3 after 6 and 12 months. After 12 months, graft endothelial cell density had decreased by 58% in the DMEK group and by 59% in the DSAEK group. The proportion of patients requiring a rebubbling were 63% in the DMEK and 64% in the DSAEK group. No lamellar graft rejection occurred in either trial arm. Conclusions: Both DMEK and DSAEK significantly improved visual acuity in patients after PK. Lamellar graft survival, loss of endothelial cells, and mean rebubbling rates were similar in both groups.